Factors Related to Stress Levels in Pregnant Women During Childhood - Sutrini Rone; Rifzul Maulina (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Pregnancy can trigger a maturity crisis that can cause stress. Stress in pregnant women is related to stress during pregnancy, childbirth, and postpartum. The purpose of this study was to examine factors related to stress levels in pregnant women facing childbirth. This type of research was an analytical survey with a cross-sectional approach conducted in the Lubuk Buaya Community Health Center Work Area from April 25 to May 7, 2022. The population was all pregnant women who visited the Lubuk Buaya Community Health Center Work Area in Padang in 2022, totaling 178 people, with a sample of 64 people, using an accidental sampling technique. Data were collected using a questionnaire with a validity analysis result of r>0.267 and a reliability test with a Cronbach's Alpha value>0.7. They were processed manually, using univariate and bivariate analysis with the chi-square test. The results of the study showed that 26.6% experienced moderate stress, 37.5% had poor family support, 37.5% had poor husband support, 40.6% had trauma, 46.9% had a personal readiness level in the unprepared category, and 46.9% had a heavy activity level. There is a relationship between family support and stress levels, there is a relationship between husband support and stress levels, there is a relationship between traumatic experiences and stress levels, there is a relationship between personal readiness levels and stress levels, and there is a relationship between activity levels and stress levels.